Stress hyperglycemia ratio and the risk of new-onset chronic diseases: results of a national prospective longitudinal study - Zhuang Ma; Lanlan Wu; Zheng Huang (Cardiovascular Diabetology)
Abstract Background The stress hyperglycemia ratio (SHR), a dynamic biomarker of acute glucose dysregulation, has been established as a predictor of adverse acute outcomes. However, its longitudinal associations with chronic disease development, particularly in middle-aged and older populations, remain insufficiently characterized. Methods This nationwide prospective cohort study analyzed data from 8942 adults aged ≥ 45 years in the China Health and Retirement Longitudinal Study (CHARLS). We established 14 disease-specific cohorts to the relationship between SHR and new-onset chronic conditions. Multivariable-adjusted Cox proportional hazards models with restricted cubic splines were utilized to estimate hazard ratios (HRs) per standard deviation (SD) increase in SHR, supported by comprehensive sensitivity analyses and subgroup stratifications. Results Elevated SHR levels were significantly associated with increased risks of incident hypertension (HR = 1.30, 95% CI: 1.06–1.60; P < 0.001), dyslipidemia (HR = 1.43, 95% CI: 1.17–1.74; P < 0.001), diabetes (HR = 2.30, 95% CI: 1.82–2.91; P < 0.001), and liver disease (HR = 1.65, 95% CI: 1.21–2.26; P = 0.002). Conversely, elevated SHR levels correlated with a lower risk of lung disease (HR = 0.67, 95% CI: 0.50–0.89; P = 0.006). Restricted cubic spline analyses revealed a nonlinear relationship between SHR and diabetes risk (P-nonlinear = 0.02), while linear associations were observed for other outcomes. Subgroup analyses demonstrated consistency across demographic strata (P-interaction > 0.05). Conclusions SHR demonstrates disease-specific associations with chronic disease development, indicating its potential value as a predictive marker for clinical risk assessment. Graphical abstract